Comparison of Nonlinear Dynamic Simulation of Lyapunov Exponent for a Cam and Different Translated Followers with Clearance (Global Journals of Research in Engineering, 2019)
In this paper, a cam with translated flat-faced and roller followers are analyzed. There is a clearance between the follower and the guide. The dynamic simulation is investigated taking into account the nonlinear dynamic of Lyapunov exponent parameter. The simulation has been done by using Solidworks program. The effect of follower guides#x2019; clearances on follower non-periodicity is considered based on Lyapunov exponent technique. Nonlinear dynamic package is used to calculate largest Lyapunov exponent for different angular velocities of the cam. The power spectrum analysis of Fast Fourier Transform and phase plane contour are examined forfaced and roller followers non-periodicity. The flat- faced follower with follower guide#x2019;s clearance C=2 mm and cam rotational speed N=1200 rpm has more non-periodic motion than roller follower. The values of largest Lyapunov exponent for flat-faced follower are bigger than the values of largest Lyapunov exponent for roller follower at (C = 2 mm and N = 1200 rpm)
Keywords: nonlinear dynamic comparison; cam-roller follower; lyapunov exponent